PERAN SISTEM INFORMASI MANAJEMEN DALAM MENINGKATKAN EFEKTIVITAS PENGELOLAAN PENDIDIKAN: SEBUAH KAJIAN LITERATUR - Gizka Amalia Putri; Dewi Tsalitsul Hamidah; Diana Ratna Sari; Ahmad Ripai (Jurnal Manajemen Pendidikan, 2026)
The development of information technology is driving the transformation of education management towards a better more effective, efficient, and data-driven system. This article aims to examine the role of Management Information Systems (MIS) in improving the effectiveness of education management through a literature review approach. The method used is descriptive qualitative research with a literature review technique, through searching various recent scientific sources. Data analysis was conducted using content analysis techniques to identify and synthesize previous research findings. The results of the study indicate that Management Information Systems play a significant role in improving administrative efficiency, the quality of data-driven decision-making, transparency, accountability, and the performance of educational institutions. Management Information Systems also enable real-time data integration that supports more responsive and accurate managerial processes. However, the implementation of Management Information Systems still faces various challenges, such as limited infrastructure, low human resource competency, suboptimal data quality, and resistance to change. On the other hand, Management Information Systems have significant potential to support the digital transformation of education through technological innovation, personalized learning, and the use of data analytics.